Protective Role of Melatonin in L-Name Induced Hypertension in Male Albino Rats - Khdhr, Aveen R.; Mahmud, Almas M. R. (Science Journal of University of Zakho, 2016)
The objective for the present study is to investigate the effects of melatonin (MEL) on systolic blood pressure (SBP), some biochemical parameters; serum (malondialdehyde (MDA), superoxide dismutase (SOD), reduced glutathione (GSH), nitric oxide (NO)) in NG-nitro-L-arginine methyl ester hydrochloride (L-NAME) treated rats. The male albino rats divided into five groups treated for 4 weeks: Group 1: Control rats. Group 2: L-NAME (35 mg/100 ml drinking water). Group 3: L-NAME (35 mg/100 ml drinking water) + melatonin (30 mg/Kg diet). Group 4: L-NAME (35 mg/100 ml drinking water) + melatonin (60 mg/Kg diet). Group 5: L-NAME (35 mg/100 ml drinking water) + melatonin (120 mg/Kg diet). A significant elevation in SBP and serum MDA were detected in L-NAME treated rats. Co-administration of melatonin with L-NAME prevented increasing in SBP and serum level of MDA in a dose dependent manner. On the other hand serum levels of SOD and GSH were decreased in response to L-NAME treatment, while, co-treatment with melatonin increased SOD and GSH in a dose dependent manner. The decrease serum NO level in response to L-NAME was significantly increased by melatonin but its level was decreased by increasing melatonin doses. In conclusion: L-NAME induced hypertension model was associated with decreased NO level, interestingly; melatonin increased serum NO in L-NAME treatments, but with increasing dose of MEL, NO level was decreased. Furthermore; MEL through its antioxidant properties reduced oxidative stress and prevented lipid peroxidation.